ȘÂḤÎḤ AL-BUKHÂRÎ'S INFLUENCE ON TAFSÎR BI AL-MAʾTHÛR: Relevance and Impact in Contemporary Quranic Studies - Azizy, Jauhar; Sihabussalam, Sihabussalam; Bustamin, Bustamin; Ziyodov, Shovosil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Tafsîr bi al-maʾthûr holds a central position in Quranic interpretation as an authoritative approach grounded in transmitted sources. In contemporary Quranic studies, however, renewed debates concerning the reliability of riwâyah, the authority of hadith, and the methodological foundations of classical tafsîr underscore the urgency of reassessing the formative contributions of early scholars. This study addresses the need by examining al-Bukhârî’s role to the epistemological and methodological foundations of tafsîr bi al-maʾthûr, with particular attention to his exegetical practices in the kitâb al-tafsîr section of Șâḥîḥ al-Bukhârî. Employing a qualitative library-based approach, this article analyzes Șâḥîḥ al-Bukhârî as the primary source alongside classical and later tafsîr works grounded in the maʾthûr tradition. Data are examined using a relevance-and-impact analytical framework to assess both the immediate and enduring influence of al-Bukhârî’s contributions on the development of Quranic interpretive sciences. This approach enables an evaluation of al-Bukhârî not merely as a compiler of hadith but as a formative architect of exegetical methodology. The findings demonstrate that al-Bukhârî’s contribution to tafsîr bi al-maʾthûr extends beyond the preservation of prophetic reports. He significantly promoted institutionalizing riwâyah as a source of tafsîr, formulating methodological principles for source selection, and conceptualizing standards of authenticity that continue to inform exegetical practice. His rigorous validation of sanad established a systematic and selective model of Quranic interpretation that profoundly influenced subsequent tafsîr traditions. This study contributes to contemporary Quranic scholarship by clarifying the methodological legacy of al-Bukhârî and demonstrating its continued relevance for evaluating transmitted sources in modern interpretive debates.